Nutritional status of a young adult population in saline-prone coastal Bangladesh - Mazumder, Tapas; Rutherford, Shannon; Rahman, Syed Moshfiqur; Talukder, Mohammad Radwanur (Frontiers in Public Health, 2023)
Introduction Like many low- and middle-income countries, understanding the nutritional status of the young population in Bangladesh has had less attention. With projected climate change and associated sea level rise, the existing problem of salinity in coastal Bangladesh will significantly increase and further worsen agrobiodiversity. This research aimed to examine the nutritional status of a young population in climate-vulnerable coastal Bangladesh to inform appropriate intervention strategies to reduce the burden on health and economic outcomes. Methods A cross-sectional survey was conducted in 2014, and anthropometric measures were conducted for 309 young people aged 19–25 years in a rural saline-prone subdistrict in southwestern coastal Bangladesh. Body mass index (BMI) was calculated from body height and weight, and data about socio-demographic factors were collected. To identify the socio-demographic risk factors affecting undernutrition (BMI <18.5 kg/m2) and overweight/obesity (BMI ≥ 25.0 kg/m2), multinomial logistic regression analysis was used. Results Overall, one-fourth of the study population was classified as underweight, and nearly one-fifth were overweight or obese. The proportion of underweight was significantly higher in women (32.5%) compared to that of men (15.2%). Overall, employment, especially in women, was associated with reduced odds of being underweight (adjusted odds ratio—aOR: 0.32; 95% confidence interval - CI: 0.11, 0.89). Subjects with secondary education incomplete (grades 6-9) compared to those with primary or below education (grades 0-5; aOR: 2.51; 95% CI: 1.12, 5.59) and employed compared to those unemployed groups (aOR: 5.84; 95% CI: 2.67, 12.74) were more likely to be overweight or obese in this study population. These associations were more pronounced in women. Discussion Multisectoral program strategies are required to tackle the growing burden of malnutrition (both under and overweight) in this young age group tailored to local contexts including in climate-vulnerable coastal Bangladesh.